2005
DOI: 10.3748/wjg.v11.i14.2088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the immunogenic domains in HBsAg preS1 region using overlapping preS1 fragment fusion proteins

Abstract: Eight GST fusion proteins containing overlapping preS1 fragments were prepared successfully. They were used for the study on the immunogenic dom-ains in preS1 (21-119) region. The preS1 (34-59) fragments were the major immunogenic domains in the preS1 region, and the antibodies against these fragments were speculated to be virus-neutralizing. Therefore, the incorporation of preS1 (34-59) fragments into epitope-based HBV vaccines may be efficient for enhancement of immune response. Additionally, the results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…optimization [Hu et al, 2005], both provide insight into the conformational and linear epitopes to which major antibody responses are directed during infection. Abundant immunogenic domains and B cell epitopes that exist within the preS1 region [Hu et al, 2005] may provide an alternate target to HBsAg.…”
Section: Immunological Detection Of Hbsag Mutantsmentioning
confidence: 99%
“…optimization [Hu et al, 2005], both provide insight into the conformational and linear epitopes to which major antibody responses are directed during infection. Abundant immunogenic domains and B cell epitopes that exist within the preS1 region [Hu et al, 2005] may provide an alternate target to HBsAg.…”
Section: Immunological Detection Of Hbsag Mutantsmentioning
confidence: 99%
“…Although not all NMR parameters in unison point to the same location of pre-structured regions, we were able to reasonably map out the prestructured regions or motifs. Figure 6 summarizes the location of the pre-structured motifs delineated in this study, as well as the previously suggested immunodominant or hepatocyte-binding domains (Neurath et al 1992;Barrera et al 2005;Glebe et al 2005;Hu et al 2005;Engelke et al 2006). As summarized in Figure 6 there is a general correlation between presence of the pre-structured motifs and immunogenicity or hepatocyte-binding ability in preS1.…”
Section: Discussionmentioning
confidence: 93%
“…The gray bars are for residues showing an intermediate degree of structural ordering and the hatched bars for least prestructuring residues. Shown below the amino acid sequence of preS1 are the previously reported functionally important domains; the putative hepatocyte receptor-binding domain with a green (Neurath et al 1986) or a red bar (Barrera et al 2005), hepatocyte attachment domains with blue bars (Glebe et al 2005), and an immunogenic domain with a violet bar (Hu et al 2005), respectively.…”
Section: Protein Preparationmentioning
confidence: 99%
See 2 more Smart Citations